Surface velocity and ice discharge of the ice cap on King George Island, Antarctica - Osmanoğlu, B.; Braun, M.; Hock, R.; Navarro Valero, Francisco José (Annals of Glaciology, 2013)
Glaciers on King George Island, Antarctica, have shown retreat and surface lowering in recent decades, concurrent with increasing air temperatures. A large portion of the glacier perimeter is ocean-terminating, suggesting possible large mass losses due to calving and submarine melting. Here we estimate the ice discharge into the ocean for the King George Island ice cap. L-band synthetic aperture radar images covering the time-span January 2008 to January 2011 over King George Island are processed using an intensity-tracking algorithm to obtain surface velocity measurements. Pixel offsets from 40 pairs of radar images are analysed and inverted to estimate a weighted average surface velocity field. Ice thicknesses are derived from simple principles of ice flow mechanics using the computed surface velocity fields and in situ thickness data. The maximum ice surface speeds reach mayor que 225 m/yr, and the total ice discharge for the analysed flux gates of King George Island is estimated to be 0.720+/-0.428 Gt/yr, corresponding to a specific mass loss of 0.64+/-0.38 m w.e./yr over the area of the entire ice cap (1127 km2).